Digital Marketing Utilization Determinants: Study on MSEs in Salatiga City - Fevriera, Sotya; Saraswati, Birgitta Dian; Adhitya, Dhian; Siwi, Virgiana Nugransih; Wahyudi*, Yustinus (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research aims to identify the factors influencing the use of digital marketing by Micro, Small, and Medium Enterprises (MSMEs) and to examine the factors affecting the preference for digital marketing usage by MSMEs in the city of Salatiga. The research sample consists of 135 business units representing MSMEs in Salatiga. Data analysis techniques involve descriptive statistical analysis, qualitative analysis, binomial and multinomial logistic regression. The research findings provide evidence of the implementation of the UTAUT theory, particularly concerning performance expectations and facilitating conditions, significantly influencing the probability of digital marketing usage and the marketing of business products. Surprisingly, acceptance as part of performance expectations has a negative impact on digital marketing usage, especially on social media platforms. Furthermore, digital marketing proves to be of paramount importance for MSMEs looking to expand their businesses. Keywords: MSMEs; Digital Marketing; Covid-19; UTAUT Theory; Logistic Regression